MANAGEMENT OF PSORIASIS: A FOCUS ON PHYTOCHEMICALS - PADMINI IRIVENTI; Vishal Gupta, N; VISHAL GUPTA N (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Psoriasis is a hyperproliferative, autoimmune skin disorder. There are several therapeutic agents used topically and systemically, but they have adverse effects. It has been reported that beta-blockers intensify psoriatic plaque and decrease the concentration of intracellular cyclic adenosine monophosphate (cAMP). In the psoriatic epidermis, the level of cAMP decreases. Caffeine is a methylxanthine that inhibits phosphodiesterase enzyme and results in a higher concentration of intracellular cAMP. Adding caffeine to topical skin treatments would be a simple way to reduce inflammation in patients with psoriasis. Furthermore, phenolic acids like chlorogenic acid (3-CQA) have recently gained substantial attention due to their various biological and pharmacological effects. Curcumin (dihydroferuloyl-methane) is a flavonoid that possesses anti-inflammatory, antitumor, and antioxidative properties. Cell proliferation arrest is caused by curcumin and apoptosis is induced in several types of human and animal cells. Imiquimod‐induced murine psoriasis is most used animal models to study this disease, due to the usage of healthy mice. Xenotransplants of human psoriatic skin in immunodeficient mice were the first approach for the association of immunologic problems with the development of psoriasis and have been also useful for the evaluation of new therapeutic agents.